Understanding Primary Curriculum from Philosophical Perspectives - Ranjitkar, Kiran Ram (Interdisciplinary Research in Education, 2021)
This paper is an attempt to understand philosophy / ideology hidden behind the present primary education curriculum of Nepal. The study was based on analysis of written curriculum published by Government of Nepal, Curriculum Development Center, Sanothimi. I applied the conceptual content analysis approach for the purpose of this study. My literature review consisted of general philosophies namely idealism, naturalism, realism, pragmatism and existentialism   and also educational philosophies such as perennialism, essentialism, progressivism and reconstructionism. Although the study focused on four elements, namely objectives, contents, teaching learning activities and evaluation process of curriculum, I made a brief analysis of aim, and contents of primary level as a whole. The current primary education curriculum is the mix of more than on philosophies emphasizing traditional ones, perennialism, and essentialism. I found negligible importance is given to critical components of learning therefore this component should be given more importance.